GARAP GERAK TARI KIJANG KENCANA DALAM EPISODE HILANGNYA DEWI SINTA SENDRATARI RAMAYANA PRAMBANAN YAYASAN RARA JONGGRANG - Kawuryansih Widowati (Institut Seni Indonesia Surakarta, 2015)
The aim of this research is to describe the treatment of the movements in the Kijang Kencanadance, including the form of the performance of the particular episode entitled Dewi Sinta’s Disappearance, the different elements of treatment of the dance movements in the Kijang Kencanadance, and an analysis of the movements. The method used in the research is a qualitative methodand the data obtained was descriptive in nature. The data obtained was processed and analyzed ina qualitative manner. The treatment of the movements in the Kijang Kencana dance is analyzedwith reference to the treatment of the dance movements found in the performance of the RamayanaDance-drama by the Rara Jonggrang Foundation in Prambanan. The analysis of these movementsuses a theory of treatment, or garap, and theories of distortion and stylization. The Kijang Kencanadance is a dance in which the patterns of movement imitate the patterns of movement in the dailylife of a deer (kijang). This imitation of the pattern of movements subsequently undergoes adistortion and stylization to become the movements that are seen in the Kijang Kencana dance inthe episode Dewi Sinta’s Disappearance in the Ramayana Dance-drama.Keywords: Episode DewiSinta’s Disappearance, Kijang Kencana, and treatment.